Modern industrial microbiology and biotechnology - Okafor, Nduka (Science Publishers, 2007)
This book is directed towards undergraduates and beginning graduate students in microbiology, food science and chemical engineering. Those studying pharmacy, biochemistry and general biology will find it of interest. The section on waste disposal will be of interest to civil engineering and public health students and practitioners. For the benefit of those students who may be unfamiliar with the basic biological assumptions underlying industrial microbiology, such as students of chemical and civil engineering, elements of biology and microbiology are introduced. The new elements which have necessitated the shift in paradigm in industrial microbiology such as bioinformatics, genomics, proteomics, site-directed mutation, metabolic engineering, the human genome project and others are also introduced and their relevance to industrial microbiology and biotechnology indicated. As many references as space will permit are included. The various applications of industrial microbiology are covered broadly, and the chapters are grouped to reflect these applications. The emphasis throughout, however, is on the physiological, biochemical principles, and where possible, the genomic principles behind these applications.